A study on the impact of foreign direct investment, exchange rate, inflation and unemployment towards economic development in Malaysia / Zhafirul Raqib Rahman and Nur Syahira Mohd Rashid - Rahman, Zhafirul Raqib; Mohd Rashid, Nur Syahira (Faculty of Business and Management, 2016)
The purpose to conduct this study is to investigate the relationship between Foreign Direct Investment (FDI), exchange rate, inflation and unemployment toward economic development in Malaysia. It covers the period 1983 until 2014, a period of 30 years. Simply, those determinants are considered as indicators for economic development in Malaysia and it has been investigated quarterly. Foreign Direct Investment has a strong influence toward economic growth in Malaysia. This determinant plays a vital role in strengthen Malaysia’s economy until Malaysia became a leader in economic growth among Asian region especially in export sectors. Same goes to the exchange rate where it also influences the economic development in Malaysia. Exchange Rate (ER) indicates a price of one country in relation to other countries in the world which means that it will related to the economic development of the country. Besides that, Inflation is an increment in the price of goods and services which will affect consumer purchasing power. Additionally, resources of labor that inefficiently used will increase the rate of unemployment. Statistics of unemployment in economics scale is used to measure the condition and extent of joblessness within an economy.